(untitled) (Journal of Parents and Teachers, 2014)
The following article offers eleven tips on what to do before, during and after the visit to the museum with the children to make it interesting and not tedious. Some examples of this are: choosing the museum to visit, controlling the time of the visit, proposing some activity for them, etc.